Biomarkers in spinal muscular atrophy - Yan, Liping; Zhang, Jinping; Zheng, Jian; Hao, Hua (Frontiers in Neurology, 2025)
Spinal muscular atrophy is a hereditary disorder leading to severe neuromuscular impairment. With the introduction of disease-modifying therapies in recent years, the role of biomarkers has expanded from aiding diagnosis to monitoring treatment responses, prognostic assessment, and the development of individualized treatment strategies. This review systematically summarizes biomarkers in the field of spinal muscular atrophy, including physiological indicators, functional assessments, imaging features, and molecular markers, which are derived from the analysis of different tissues from human patients and animal models. This article provides a concise summary of the classic biomarkers widely used in current clinical practice and introduces the potential new biomarkers revealed by the latest research. It focuses on discussing the expression patterns, clinical correlations, and applicable conditions of various types of biomarkers, with the aim of providing more accurate basis for disease stratification, efficacy prediction, and treatment decision-making.